DESAIN BERKELANJUTAN DAN PELUANG PASAR EKSPOR PRODUK HOME DÈCOR INDONESIA DI JERMAN - Nadya Megawati Rachman; Ratnaningsih Hidayati (Fakultas Ekonomi Universitas Negeri Medan, 2022)
Indonesian home décor products produced by Small and Medium Enterprises (SMEs) have a relatively stable export market share in Germany. This study aims to analyze the export market potential of Indonesian home décor products in the German market. and explain the concepts of integrating sustainable design into Indonesian home décor products. The research was conducted with a qualitative approach, namely by conducting desk research on data related to the export of Indonesian home décor products and also reviewing the literature on relevant sources. The results of the study show that Indonesia still has the opportunity to increase its export market share for home décor products with the HS code 462090. The recommended export marketing strategy is that SME producers should focus on middle and upper class customer segments who have a preference for sustainable designs. The government, both at the local and national levels, should also be able to support producer SMEs to be able to compete and produce home décor products with high quality and competitiveness.